Surfactant for the treatment of respiratory distress syndrome in very low birth weight infants at a level 2 hospital: a descriptive retrospective cohort study – safety and efficacy - Nxumalo, Mnqobi (Department of Paediatrics and Child Health, 2024)
Abstract: Background and rationale: Respiratory Distress Syndrome (RDS) is common in pre-term infants and is related to immaturity of the lungs. Surfactant therapy is now being widely used outside of tertiary neonatal centres. The purpose of this study is to describe the demographics and the incidence of adverse events in very low birth weight preterm infants with Respiratory Distress Syndrome (RDS) treated with surfactant at a regional Hospital in the Western Cape Province of South Africa. Methods: This was a retrospective observational study of infants treated with surfactant during the study period 2017 to 2019 at George Regional Hospital. We conducted an electronic folder review of infants with a birth weight of 800g to 1200g. Outborn infants and those with congenital abnormalities were excluded. Results: The total number of patients included in the study was 66. The median birth weight was 965g (Interquartile range (IQR) 880-1060g) with a median gestational age of 28 weeks (IQR 28-29 weeks. The median time to first dose of surfactant was 5 hours (IQR 2-16). The mortality rate was 17(25.8%). The incidence of Bronchopulmonary dysplasia was 4(6%).The incidence of pulmonary air leak was 2(3%) and pulmonary haemorrhage was 6(9.1%). The median number of days on mechanical ventilation for the patients who were ventilated was 3 days (IQR 2-6). The median total number of days on respiratory support was 9 days (IQR 4- 29). Conclusion and recommendations: Regional hospitals have limited capacity for ventilatory support of preterm newborns. The mortality rate was comparable to outcomes at South African central hospitals. Further research should explore how the incidence of adverse events can be reduced in very low birth weight infants.